RAINFALL AND RAINY DAYS TRENDS IN CONTEXT OF CLIMATE CHANGE OVER SAUDI ARABIA : A CASE STUDY OF HA’IL REGION - Salah Abdulmohsin As-Shamari (Engineering Heritage Journal)
This study used the recorded daily rainfall, available and monitored during 38 years (from January 1, 1978 to December 31, 2015) in total of 8 rain stations and the meteorology station of Ha’il. The purpose of this study is to analyze the variations and trends of rainfall events through a statistical analysis of data recorded. The analyze the rainfall variability has been processed using the coefficient of variation (CV) and Standardized Analyze Index (SAI) and plotted. While the rainfall trends have been analyzed by three statistically methods widely used: Simple Moving-Average (SMA), Homogeneity of variance (Hartley’s Fmax-ratio) and Semi-averages. The trends analysis of rainfall show that the fluctuations or variations in climatic parameters is a recurring phenomena in the studied stations. Inter-annual variability of rainfall and the cumulative frequency of rainy days are characterized by the high coefficients of variation. In addition, the values of Chi square test reveals the significant Standardized Anomaly Index (SAI) of rainfall. Accordingly, the results contain a total of 18 increasing trends (37.5%) and 30 decreasing trends (62.5%). These results indicate that the aspects of climate change in Ha’il region accelerating in recent decades. This situation may have severe socioeconomic repercussions in many sectors especially the agriculture and surface water resources.